2016
DOI: 10.1080/10538712.2016.1158762
|View full text |Cite
|
Sign up to set email alerts
|

Investigative Interviewing of Aboriginal Children in Cases of Suspected Sexual Abuse

Abstract: This study examined the investigative interviewing of Australian Aboriginal children in cases of alleged sexual abuse, with a focus on three commonly included components of interview protocols: ground rules, practice narrative, and substantive phase. Analysis of 70 field transcripts revealed that the overall delivery and practice of ground rules at the beginning of the interview was positively associated with the spontaneous usage of rules in children's narratives of abuse. When specifically examining the "don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The analogy of appropriate and inappropriate approaches used by interviewers in Cyprus is in agreement with the amount of appropriate and inappropriate approaches used by interviewers in other countries such as Australia (Hamilton et al 2016), Canada (Gagnon and Cyr 2017), Estonia (Kask 2012), Finland (Korkman et al 2006), New Zealand (Wolfman et al 2016), Norway (Thoresen et al 2006) and Sweden (Cederborg et al 2000). Thus, the quality of police interviews in Cyprus is similar to those in other countries.…”
Section: Appropriate Approaches Based On Interviewer Working Hourssupporting
confidence: 73%
“…The analogy of appropriate and inappropriate approaches used by interviewers in Cyprus is in agreement with the amount of appropriate and inappropriate approaches used by interviewers in other countries such as Australia (Hamilton et al 2016), Canada (Gagnon and Cyr 2017), Estonia (Kask 2012), Finland (Korkman et al 2006), New Zealand (Wolfman et al 2016), Norway (Thoresen et al 2006) and Sweden (Cederborg et al 2000). Thus, the quality of police interviews in Cyprus is similar to those in other countries.…”
Section: Appropriate Approaches Based On Interviewer Working Hourssupporting
confidence: 73%
“…Even after the introduction of interviewing manuals, most interviews in most countries have still relied on inappropriate approaches to gain information from children (e.g. Hamilton et al 2016;Wolfman, Brown & Jose, 2016). Implementing IGIpop alongside these manuals and training may help improve the quality of investigative interviews further.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate approaches are approaches which are more likely to gain reliable details . When analyzing the approaches used in interviews it has been shown that the percentage of inappropriate approaches is often higher than appropriate approaches when interviewing children in Australia (Hamilton, Brubacher & Powell, 2016), in Canada (Gagnon & Cyr, 2017), in Estonia (Kask, 2012), in Finland (e.g. Korkman, Santtila & Sandnabba, 2006), in New Zealand (e.g.…”
Section: Why Consider Talent Management In Investigative Interviews Of Children?mentioning
confidence: 99%
“…The neglect-focused articles explore associated risk factors, articulate divergent perceptions and definitions of neglect, and examine implications for Indigenous children (Evans-Campbell, 2008;Nelson et al, 1996;Newton, 2017;Slee, 2001). The research focusing on sexual abuse covers topics such as the correlates of sexual abuse, divergent perceptions and experiences of disclosing sexual abuse, the ways in which both communities and legal institutions silence and marginalize victims, and a lack of appropriate services in Indigenous communities (Bailey et al, 2015;Hamilton et al, 2016;Hodgson, 1990;Smallwood, 1995;Stanley et al, 2003). A handful of articles also focus on more specific topics such as maltreatment related injury (O'Donnell et al, 2010;Pike & First Nations and Inuit Child and Youth Injury Indicators Working Group, 2011).…”
Section: Forms Of Maltreatmentmentioning
confidence: 99%